Réponses

2014-05-28T10:23:34+02:00
a)
- 3x + 5 = x - 3
- 3x - x = - 3 - 5
- 4x = - 8
x = 8/4
x = 2

b)
7x - 5 = - 3 (5x - 4)
7x - 5 = - 15x + 12
7x + 15x = 12 + 5
22x = 17
x = 17/22

c)
- 4 (5x - 6) + 9 = - 10x - 18
- 20x + 24 + 9 = - 10x - 18
- 20x + 10x = - 18 - 24 - 9
- 10x = - 51
x = 51/10

d)
7x + 4 (- 2x + 3) = - 5x - 3
7x - 8x + 12 - 5x - 3
7x - 8x - 5x = - 3 - 12
- 6x = - 15
x = 15/6

e)
- 2 (- 3x - 1) + 8x - 6 = 7x - (5 - x)
6x + 2 + 8x - 6 = 7x - 5 + x
6x + 8x - 7x - x = - 5 - 2 + 6
6x = - 1
x = - 1/6

f)
3/4x + 2/3 = 2x + 7/6
9/12x + 8/12 = 24/12x + 14/12
9/12x - 24/12x = 14/12 - 8/12
- 15/12x = 6/12
- x = 6/12 x 12/15
- x = 72/180
x = - 2/5
2014-05-28T10:41:11+02:00
A) -3x+5=x-3
-3x-x = -3-5
-4x =-8
x = -8/-4
x = 2

b)7x-5=-3(5x-4)
7x-5 = -15x+12
7x+15x = 12+5
22x = 17
x = 17/22

c)-4(5x-6)+9=-10x-18
-20x+24 = -10x-18
-20x+10x = -24-18
-10x = -42
x = -42/-10
x = 42/10

d)7x+4(-2x+3)=-5x-3
7x-8x+12 =  -5x-3
-x+12 = -5x-3
-x+5x = -12-3
4x = -15
x = -15/4
e)-2(-3x-1)+8x-6=7x-(5-x)
6x+2+8x-6 = 7x-5+x
14x-4 = 8x-5
14x-8x = -5+4
6x = -1
x = -1/6
f)3 sur4x+2 sur 3=2x+7 sur6
3/4x + 2/3 = 2x + 7/6
3*3/3*4x +  2*4x/3*4x = 12x/6 +7/6
(9+8x)/12x = (12x+7)/6
(9+8x)/2x = 12x+7
9+8x = 2x(12x+7)
9+12x = 24x
²+14x
24x²+14x-12x-9 = 0
24x²+2x-9 = 0